Nanocrystalline Zn0.9Mn0.1S Thin Film : Case Studies - Mohammad Syuhaimi, Ab-Rahman; Noor Azie Azura, Mohd Arif; Abang Annuar, Ehsan; Sahbudin, Shaari (Science Publications, 2011)
Problem statement: The high quality of ZnS:Mn nanocrystals is important in nanotechnology industries. The perfect chemical procedure is significant to produce the best of nanocrystals. Hence, this research is concern on the good chemical method in processing manganese doped zinc sulphide nanocrystals. Approach: For the first step, Mn doped ZnS nanocrystals were synthesized by using sol gel spin coating method. After the crystals were obtained, the properties of ZnS:Mn2+ on morphology, optical and electrical were determined by using Field Emission Scanning Electron Microscopy (FE-SEM), Ultra Violet Visible Spectroscopy (UV-Vis), Photoluminescence Spectrophotometer (PL) and current-voltage measurement (I-V). Results: The particle has diameter size around 22 nm. In this experiment it was found that the current increases with the increasing of applied voltage (-10 V to 10 V). UV-Vis spectra shows appearance of an absorption peak at 250 nm meanwhile in PL analysis spectra, the sample has been recorded at room temperature and two emissions peaks at blue and orange emissions were observed. Conclusion: Manganese doped zinc sulphide was successfully synthesized using sol gel spin coating method and it performs in good quality. Key words: Sol gel, spin coating, zinc sulphide, manganese, optical, electrical